Effects of CSR and CR on business confidence in an emerging country - Del Brio, Jesús (2020)
Corporate social responsibility has been one of the main pillars of development for companies in developed countries and studies are being conducted for developed countries and the productive sector of the economy. Therefore, the main objective of this paper is to analyze the relationship between corporate social responsibility (CSR), corporate reputation (CR), and business confidence in the context of the banking sector in an emerging country (Peru). To test the hypotheses presented in this paper, we sent a survey to 1745 banking executive officers of the branch offices in Peru. These key individuals were selected as the target population of the study because the authors sought to study the management’s perception of CSR and business confidence. From the data obtained from the survey, it has been determined that the strategic consideration of CSR in Peruvian banks directly influences the perception of business confidence. Secondly, it has been demonstrated that the strategic consideration of CSR in Peruvian banks positively influences corporate reputation and, finally, the perception of the importance of the corporate reputation of Peruvian banks and significantly influences the perception of business confidence by the managers. The main contribution of this paper is that it analyzes empirically how business confidence is perceived by managers, who are the main agents involved in implementing CSR actions, based on their opinion of the strategic consideration of CSR and the perception of CR in a context barely investigated, an emerging country.